An introduction to e-SSC test kit as a new technique to characterize swelling and shrinkage potential of rock material / Intan Shafika Saiful Bahri ... [et al.] - Saiful Bahri, Intan Shafika; Mohamed, Zainab; Ramli, Rozaini; Mior Abas, Mohd Hidayat (Universiti Teknologi MARA Pulau Pinang, 2011)
The strength and deformation characteristics of rock masses are required for almost any form analysis used for the design of slopes.